A companion to motion pictures and public value - Hjort, Mette; Nannicelli, Ted (John Wiley & Sons, 2022)
This volume's topic, the varied intersections and conjunctions of motion pictures and public value, is somewhat daunting in its potential scope. As the table of contents indicates, the book is structured in terms of (a non-exhaustive list of) different sorts of value that, we claim, can be understood as yielding public value or values that are partly constitutive of a common good. Given the breadth and heterogeneity of the contributions collected here, organised in seven different sections, our discussion in this main introduction will remain quite general. Each section of the book is preceded by a section introduction, in which we outline the main themes of the section and draw some connections between the individual chapters therein. For now, then, we will aim to do just two things. First, we will sketch a bit of background context for the project, outline its aims, and describe the approaches that characterise the contributions to the volume. Then, we will explain how we are conceiving of the concepts of 'motion pictures,' 'value,' and 'public value' respectively"--